The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10533-009-9319-7
|View full text |Cite
|
Sign up to set email alerts
|

Compositional changes in fish scale hydroxylapatite during early diagenesis; an example from an abandoned meander

Abstract: The chemistry of recent fish scales (tench, common carp, amur and European perch) and subrecent fish scales (European perch and mostly taxonomically not determined) was studied by means of laser ablation inductively coupled plasma mass spectrometry and electron microprobe from shallow boreholes in the abandoned meander Certak near Uherské Hradiste. A detailed study of subfossil fish confirms extremely rapid changes in the chemical composition of hydroxylapatite during very early diagenetic processes in the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 91 publications
(114 reference statements)
2
12
0
Order By: Relevance
“…These data indicate that the chemistry of the hydroxyapatite in the scale structure reacts differently to the other fish hard-parts when heated. The alkaline earth elements, Mg and Sr were greater in the treatment groups, suggesting that the use of Sr as a palaeothermometer in scales is problematic, in agreement with Kalvoda et al (2009), who found that early diagenetic alteration in fish scales is so profound that palaeoecological interpretations are not possible. Differences may also reflect that scales are in direct contact with the environment unlike otoliths and vertebrae.…”
Section: Res 25supporting
confidence: 82%
“…These data indicate that the chemistry of the hydroxyapatite in the scale structure reacts differently to the other fish hard-parts when heated. The alkaline earth elements, Mg and Sr were greater in the treatment groups, suggesting that the use of Sr as a palaeothermometer in scales is problematic, in agreement with Kalvoda et al (2009), who found that early diagenetic alteration in fish scales is so profound that palaeoecological interpretations are not possible. Differences may also reflect that scales are in direct contact with the environment unlike otoliths and vertebrae.…”
Section: Res 25supporting
confidence: 82%
“…These energy ranges also show up as green and red flecks in patches of quartz ("Q" on Figure 7A), suggesting that the quartz patches are polycrystalline, and that the quartz grains are randomly oriented. Whilst hydroxyapatite is a common component of fish scales (Lanzing and Wright 1976;Ikoma et al 2003;Kalvoda et al 2009), these scales are practically invisible on the fossil itself. It is not clear whether the scales have simply been preserved in a way that is not visibly obvious, or whether they are preserved beneath a thin layer of limestone, but given the low atomic number of P and the low energy of X-rays it emits, we would expected that P-derived X-rays would be attenuated by just a few micrometers of overlying material and it is more likely that the scales have been preserved but are almost invisible to the naked eye.…”
Section: Crystallographic Contrast Imagingmentioning
confidence: 99%
“…Bioapatites usually display small particle sizes and significant carbonate contents [15,52]. In addition, apatite particles in bones of living animals are coated by a poorly-ordered hydrous phosphatic phase [53] and associated with organic polymers (collagen), which transform [54] or decay after an animal's death [55]. In contrast, carbonate-fluorapatite is less soluble than bioapatite [26,54] and often represents an ultimate stage of recrystallization of biomineralized anatomical structures in geological environments [26,28,52,54,56].…”
Section: Preservation Versus Recrystallization Of Triazeugacanthus Timentioning
confidence: 99%
“…In addition, apatite particles in bones of living animals are coated by a poorly-ordered hydrous phosphatic phase [53] and associated with organic polymers (collagen), which transform [54] or decay after an animal's death [55]. In contrast, carbonate-fluorapatite is less soluble than bioapatite [26,54] and often represents an ultimate stage of recrystallization of biomineralized anatomical structures in geological environments [26,28,52,54,56]. Carbonate-fluorapatite also occurs in sedimentary environments as an authigenic mineral, likely produced from the bacterial decay of organic matter [57][58][59][60].…”
Section: Preservation Versus Recrystallization Of Triazeugacanthus Timentioning
confidence: 99%